2012
DOI: 10.1021/nl300973b
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controlled Model Co Nanoparticle Catalysts for CO2 Hydrogenation: Synthesis, Characterization, and Catalytic Reactions

Abstract: Model cobalt catalysts for CO 2 hydrogenation were prepared using colloidal chemistry. The turnover frequency at 6 bar and at 200−300°C increased with cobalt nanoparticle size from 3 to 10 nm. It was demonstrated that near monodisperse nanoparticles in the size range of 3−10 nm could be generated without using trioctylphosphine oxide, a capping ligand that we demonstrate results in phosphorus being present on the metal surface and poisoning catalyst activity in our application.KEYWORDS: Cobalt nanoparticles, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(190 citation statements)
references
References 26 publications
14
172
2
2
Order By: Relevance
“…Along with the development of nanotechnology, catalytic reactions regarded as structure-insensitive using nanoparticles with broad size distribution, turned out to become structure-sensitive reaction with well-defined nanoparticles. Recently, monodisperse Co nanoparticles with sizes ranging from 3 to 10 nm showed size-dependent activity enhancement of CO 2 hydrogenation which was an analogous reaction of Co catalyzed Fischer-Tropsch reaction [12]. The turnover frequency of CO 2 hydrogenation was significantly higher on the larger Co nanoparticles, which was in good agreement with the values reported for an incipient wetness impregnation prepared catalyst.…”
Section: Size-and Shape-dependent Catalytic Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…Along with the development of nanotechnology, catalytic reactions regarded as structure-insensitive using nanoparticles with broad size distribution, turned out to become structure-sensitive reaction with well-defined nanoparticles. Recently, monodisperse Co nanoparticles with sizes ranging from 3 to 10 nm showed size-dependent activity enhancement of CO 2 hydrogenation which was an analogous reaction of Co catalyzed Fischer-Tropsch reaction [12]. The turnover frequency of CO 2 hydrogenation was significantly higher on the larger Co nanoparticles, which was in good agreement with the values reported for an incipient wetness impregnation prepared catalyst.…”
Section: Size-and Shape-dependent Catalytic Propertiessupporting
confidence: 81%
“…Transition metal nanoparticles including Co and Fe can be obtained through thermal decomposition by injection of organometallic precursors such as dicobalt octacarbonyl and iron pentacarbonyl into the surfactant solution at an elevated temperature [11]. The size of Co nanoparticles can be varied from 3 to 10 nm by the temperature of the oleic acid solution, when the Co precursor is injected rapidly [12]. In order to synthesize small nanoclusters less than 1 nm, a dendrimer which is a macromolecule with a central core surrounded by hyper-branched repeating units can be used as a template as well as a stabilizing agent [13].…”
Section: Metal Nanoparticles With Controlled Size and Shapementioning
confidence: 99%
“…16 The use of nanomaterials to address questions specifically in the study of cobalt based catalysts for Fischer Tropsch has recently been reviewed, 17 and we have already used size controlled cobalt nanoparticles to explore particle size effects in CO 2 hydrogenation. 18 To understand better the exact role of precious metals in these types of catalysts, we have recently reported on the preparation of Pt-Co bimetallic nanoparticles, where each nanoparticle contains an approximately 1:1 atomic of the two metals. However, we found that these particles were poor CO 2 methanation catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Here, however, we preactivated the cobalt catalyst by reduction at 450 °C in H 2 , a treatment anticipated to afford fully reduced cobalt nanoparticles -we have previously reported a water loss / hydrogen adsorption temperature programmed reduction peak at this temperature for pure cobalt nanoparticle based catalysts. 18 Oxidation by water (a reaction product) is often considered to be a possible deactivation mechanism during cobalt catalyzed hydrogenations, 19,20 although others have been unable to observe this during in situ NEXAFS spectroscopy of cobalt crystallites in a 1 : 1 mix of H 2 O and H 2 . 21 However, if methane (or other hydrocarbon) formation occurs after breaking carbon-oxygen bonds in CO 2 , oxygen may accumulate on (and beneath) the surface eventually leading to near surface oxidation before water is formed (Figure 3(a)).…”
Section: Introductionmentioning
confidence: 99%
“…54 Overall the ability to prepare nanoparticles of well-defined sizes (e.g. samples with a particle size distribution of only  0.5 nm 46 ) by a selection of routes has confirmed a particle size effect exists. This is likely to be important in the design of practical catalysts for FT synthesis.…”
Section: Molecular Level Understanding Of Ft Catalysis On Cobaltmentioning
confidence: 96%